Signifikasi Peran Qawa’id Fiqhiyyah dalam Pembelajaran Ekonomi Syariah - Rahmad Hakim (University of Darussalam Gontor, 2016)
Along with the development time and place, human economic life increasingly dynamic. On the other hand, the development of Islamic financial institutions is increasing and growing, especially in the last decade. Two things above be an important factor of the importance of certainty about the various forms of transactions in accordance with Islamic Shari’a. Offering hope that the development of economic life and Islamic financial institutions should increasingly all transactions with Shari’ah system. In the presence of the Islamic economic studies program or Islamic economics at Higher Education Institutions (IPT), both state and private, who have a major role in preparing the human resources, has a big responsibility to ensure legal certainty in all transactions; both traditional and contemporary transactions. With this, it is necessary for all students to learn qawa’id fiqhiyah for reaching these goals. This study used a qualitative descriptive method, that is the approach used to address the significance of the role of qawa’id fiqhiyyahin learning Islamic economics. In collecting the data used methods of documentation, namely by performing in-depth research on a variety of relevant literature in the field of qawa’id fiqhiyyah. The final conclusion of this study is that qawâ’id fiqhiyyahhave a significant role in the learning of Islamic economics. This is due to the reality of human life in the field of running dynamic economy, which often results in the release of all forms of economic activity of Islamic law. So that many transaction sprung did not have a clear legal status.